A European men's health strategy: here at last. Issue 1 (30th January 2019) - Baker, Peter
Abstract : The lack of a policy focus on men's health has held back work in the field. The adoption of the first‐ever men's health strategy by WHO Europe, and its recognition that many men's health outcomes are unacceptably poor, is therefore very significant. Here the author outlines the strategy and how it could make a difference to men's health.